ORIGINAL PAPER Carotid artery stenting with proximal or distal brain protection: a novel treatment modality in carotid occlusive disease - Pieniążek, Piotr; Musiałek, Piotr; Kabłak-Ziembicka, Anna; Przewłocki, Tadeusz; Moczulski, Zbigniew; Motyl, Rafał; Leśniak-Sobelga, Agata; Żmudka, Krzysztof; Tracz, Wiesława (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2005)
Stroke is the third commonest cause of death and a leading cause of disability. Carotid artery atherosclerosis is casually associated with 20% of strokes. Percutaneous treatment of carotid artery disease is a viable alternative to surgery, and it has recently been attracting growing attention. Material and methods: From January 2001 to April 2005 we performed carotid artery stenting (CAS) in 210 patients (57 women); mean age of 64.2±9.2 years. There were 147 (70%) symptomatic and 63 (30%) asymptomatic patients. Prior to CAS all patients underwent carotid (in most cases also intracranial) Duplex Doppler and CT angiography of supra-aortic trunks and cerebral arteries. Invasive coronary angiography showed significant coronary artery disease in 149 (71%) patients. All CAS procedures were performed with neuroprotection. Proximal (Mo.Ma or PAES) and distal (filters or occlusive balloon) neuroprotection was applied in 63 (29%) and 157 (71%) cases, respectively. Patients were evaluated at discharge and at 30 days. Results: The procedural success rate was 98.1%. There was a significant stenosis reduction (from 77.3±11.2% to 14.4±9.3% diameter stenosis, p<0.001) and a corresponding increase in minimal lumen diameter (from 1.32±0.59 mm to 3.97±0.85 mm, p<0.001). In the periprocedural period 5 (2.4%) patients had TIA and 4 (1.9%) had minor stroke (including 3 haemorrhagic strokes in the course of hyperperfusion syndrome). There was no death, major stroke or myocardial infarction within 30 days following CAS. Conclusions: Percutaneous stent-assisted carotid angioplasty is effective and features a low complication rate. Availability of several (proximal and distal) neuroprotection systems plays a key role in CAS safety.